Low driving voltage in an organic light-emitting diode using MoO3/NPB multiple quantum well structure in a hole transport layer - 穆雪 吴晓明 华玉林 焦志强 申利莹 苏跃举 白娟娟 毕文涛 印寿根 郑加金 (中国物理B：英文版, 2013)
The driving voltage of an organic light-emitting diode（OLED） is lowered by employing molybdenum trioxide（MoO3）/N,N＇-bis（naphthalene-1-yl）-N,N＇-bis（phe-nyl）-benzidine（NPB） multiple quantum well（MQW） structure in the hole transport layer.For the device with double quantum well（DQW） structure of ITO/[MoO3（2.5 nm）/NPB（20 nm）]2/Alq3（50 nm）/LiF（0.8 nm）/Al（120 nm）],the turn-on voltage is reduced to 2.8 V,which is lowered by 0.4 V compared with that of the control device（without MQW structures）,and the driving voltage is 5.6 V,which is reduced by 1 V compared with that of the control device at the 1000 cd/m2.In this work,the enhancement of the injection and transport ability for holes could reduce the driving voltage for the device with MQW structure,which is attributed not only to the reduced energy barrier between ITO and NPB,but also to the forming charge transfer complex between MoO3 and NPB induced by the interfacial doping effect of MoO3.